The Audiosphere of Roger Donaldson’s The Bounty Motion Picture in Light of the Theory of Michel Chion - Drozdowski, Tomasz (Interdisciplinary Studies in Musicology, 2025)
The study of a film audiosphere with no access to original score nor information about non-musical part of a film audio track poses quite a challenge related to numerous film works. In reference to synthesizer music, the next problem is the analysis of specific sounds and effects, achieved by composers and kept unrevealed. The paper verifies whether Michel Chion’s theory allows of analyzing film music in regard to the shortage of sources. Does the combination of this theory with the comparative method (selective auditory- descriptive analysis of film audio track versus auditory-descriptive analysis of film music itself released on albums) allow of studying film music without access to original score? The synthesis of Chion’s comprehensive theory and the term audiosphere is, in turn, a proposition that addresses the problem of definitions formulated differently by other researchers in the subject literature (in the area of both film musicology and soundscape studies). The term audiosphere (audiosfera in Polish) has significantly different meaning from soundscape concept. It comes from Polish scientific literature and has been introduced at the beginning of this research paper. Another aim of the study is to determine whether Chion’s theory remains complementary to one another with the selected research concepts. According to Chion’s theory assumptions, if music and sound are potentially equally important components of film audiosphere, may non-musical sound function analogously to theme tunes and leitmotivs? The author of this research has studied the key elements of The Bounty’s audiosphere, in relation to the selected definitions of Chion’s theory. The analysis took into account the unusual use of electronic music in historical film, the impact of non-diegetic music